PENERAPAN TEKNOLOGI BLOCKCHAIN DALAM TRANSAKSI UANG DIGITAL - Andika Mahwayudi; Muhammad Irwan Padli Nasution (Kohesi: Jurnal Sains dan Teknologi, 2025)
The application of blockchain technology in digital currency transactions has significant potential to revolutionize our interactions with money and digital assets. As a secure and transparent distributed system, blockchain offers various advantages, including transaction efficiency, high security, broader financial access, and decentralization. By eliminating intermediaries, this technology can reduce transaction costs and speed up the process. However, challenges such as security risks, scalability issues, integration with legacy infrastructure, regulatory uncertainty, and threats to data privacy need to be addressed to ensure effective implementation. This research aims to analyze the benefits, challenges, and impacts of blockchain implementation in the financial system and society as a whole, as well as to highlight the importance of understanding and collaboration in harnessing the potential of this technology for a more efficient and inclusive future. Keywords: Blockchain Technology, Digital Currency, Transactions.